Escala de reserva cognitiva : adaptação para o português brasileiro e primeiras evidências de validade - Kudiess, Thais Landenberger (2018)
Cognitive Reserve (CR) studies show that life experiences can contribute with the formation of complex cognitive processing and compensatory networks that are capable of protecting or hindering the development of cognitive impairments associated with neurocognitive diseases. As a theoretical construct, it can’t be measured directly, albeit studies addressing an approximate measure of CR are being developed. An instrument that is capable of estimating the CR might contribute on the accuracy of neurocognitive diseases’ diagnostics, the early start and planning of interventions, and protective measures supporting a healthy aging. Until now, no scale or questionnaire assessing the CR, validated for Brazil, was identified. Hence, the present dissertation aimed to develop a cross-cultural adaptation of the Escala de Reserva Cognitiva - ECR for Brazilian Portuguese and pool the initial data of evidence validity. Initially, a systematic review of the literature was performed to identify which instruments were available worldwide to assess CR and if there was any validated for Brazil. Next, the translation and cross-cultural adaptation of the ERC and initial psychometric validation studies were performed. The method comprised the following stages: 1) initial translation, 2) synthesis of the translations, 3) assessment of the translations’ synthesis by experts, 4) assessment of the instrument by the target population, 5) back-translation, and 6) psychometric study. The validation stage sample consisted of 132 community subjects, 31 adults (40-59 years old) and 101 elderly (≥ 60 years old). Internal consistency (main components analysis), internal validation (Cronbach’s Alpha), and convergent validity were performed with education, profession, and IQ. Results indicate that ERC, in its Brazilian version, presents semanthic equivalence with the original scale and adequate rates of internal consistency and convergent validity. Although these data support the usage of ERC for the Brazilian population, it is highlighted that the scale explores the engagement in daily activities that contribute with the CR, and not the construct per se. Additionally, the psychometric studies presented in this dissertation are preliminary data and more research is needed addressing the ERC in Brazil to verify and add to the presented conclusions.